PENOKOHAN KRSNA DAN BALARÄ€MA DALAM RELIEF CERITA KRSNA DI CANDI LARA JONGGRANG - Restiyadi, Andri (BRIN, 2011)
Ká¹›á¹£á¹‡a's Story Relief that carved on Lara Jonggrang Temple is an interesting relief which is rarely glimpsed as an object of research. This relief's depict Ká¹›á¹£á¹‡a and BalarÄma's life since childhood to adulthood. However, not all of the story is being carved, but the selected parts only. The aim of this research is to know how to characterize of Ká¹›á¹£á¹‡a and BalarÄma on that relief. This research will use instrinsic story builder approach that usually used in literacy criticism.